Reconstructing a national identity : the Jews of Habsburg Austria during World War I - Rozenblit, Marsha L., 1950- (Studies in Jewish history., 2001)
The Battle of Antietam, fought on September 17, 1862, was the bloodiest single day in American history, with more than 6,000 soldiers killed--four times the number lost on D-Day, and twice the number killed in the September 11th terrorist attacks. In Crossroads of Freedom, America's most eminent Civil War historian, James M. McPherson, paints a masterful account of this pivotal battle, the events that led up to it, and its aftermath. As McPherson shows, by September 1862 the survival of the United States was in doubt. The Union had suffered a string of defeats, and Robert E. Lee's army was in.